AN ONLINE MOODLE EXPERIENCE IN PHYSICS AT HIGHER SECONDARY LEVEL - G, Manoj Praveen (SCHOOL SCIENCE, 2018)
The researcher reports the use of a Moodle platform for designing a Problem-Solving Learning Environment to teach solving of problems in physics. The sample consisted of 113 higher secondary students of Class XI who were taught solving of problems using an instructional module with the schema based problem solving method on Moodle. The instructional module addresses all the problem types for the topic ‘One Dimensional Motion’ as prescribed in the NCERT textbooks of Class XI. A feedback of the learners regarding the user friendliness, effectiveness and drawbacks of the course was analysed. This was compared with the feedback of another group taught with the same framework of problem solving learning environment without Moodle support. The effect of using Moodle as a courseware on Problem-Solving Ability was studied. For this, a quasi-experimental study was designed with two experimental groups and a control group. The first group was taught with schema based instruction with Moodle, the second group was taught schema based instruction without Moodle and the third group was taught using drill method. A one way ANCOVA was performed to determine if a statistically significant difference existed between the methods of instruction on the Problem-Solving Ability controlling for Nonverbal Intelligence and Logical-Mathematical Intelligence. The ANCOVA results reveal that schema based instruction using Moodle significantly increases the gain in Problem Solving Ability compared to schema based Instruction without Moodle and the drill method of teaching problem solving.